THE EVOLUTION OF WAGES IN THE REPUBLIC OF MOLDOVA. THEIR IMPACT ON THE FUNCTIONALITY OF THE LABOR MARKET - VACULOVSCHI DORIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
The consolidation of economic market relations in the Republic of Moldova led, on the one hand, to the diversification of the population's income forms, and on the other hand, to the reduction of the role of the salary in the formation of the population's income. Against the background of inflationary processes, privatization processes, other economic transformations in the context of the transition to the market economy of the 90’s, there was a continuous process of reduction of the real wages of workers. Diminishing of the role of wages in the formation of the disposable income of the population in favour of other sources of income is a natural process under the conditions of the transition to the market economy. But when this decrease takes uncontrolled proportions, there can be a transfer of the reproduction function of the labor force from the salary to other forms of income, which are not directly related to a productive activity, such as the work activity. There is a worsening of the situation on the labor market, which manifests itself through a drastic decrease in occupational indicators, thus undermining the functioning mechanism of the national economy and the development of the existing human potential. In the situation where the salary no longer fulfils its basic economic and social functions, i.e. reproduction, motivation, stimulation of economic growth, the population no longer connects their work and employment needs to the labor market of the Republic of Moldova choosing labor markets from other countries where the salary conditions are more favourable. This fact has led to the intensification of international labor migration.